2014
DOI: 10.1155/2014/521602
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Xuefu Zhuyu Tang for Patients with Angina Pectoris: A Meta‐Analysis and Systematic Review

Abstract: Objective. To evaluate the efficacy of Xuefu Zhuyu Tang (XFZYT) for treating angina pectoris (AP). Methods. Six databases were searched (up to December, 2013). Eligible randomized controlled trials (RCTs) evaluating the efficiency of XFZYT plus traditional antianginal medications (TAMs) compared with TAMs alone in patients with AP were included. The outcomes were relief of anginal symptoms (RAS) and improvement of electrocardiogram (ECG) and blood high-density lipoprotein cholesterol (HDL-C) level. Result. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In practice, the use of these formulae depends on the location of stasis. The prescription of TQHXT focuses on the area above the neck [21], and XFZYT focuses on the chest [22,23]. As for GXZYT, it is commonly used to treat the stasis occurring between the diaphragm and lower abdomen [24], and STZYT is utilized to remove the stasis on the limbs and musculoskeletal system [25].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the use of these formulae depends on the location of stasis. The prescription of TQHXT focuses on the area above the neck [21], and XFZYT focuses on the chest [22,23]. As for GXZYT, it is commonly used to treat the stasis occurring between the diaphragm and lower abdomen [24], and STZYT is utilized to remove the stasis on the limbs and musculoskeletal system [25].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, combination therapy with Xuefu Zhuyu decoction and traditional antianginal medications (TAMs) was more effective in treating angina pectoris than TAMs alone. Evidence has indicated that Xuefu Zhuyu decoction combined with TAMs was more effective in improving RAS (RR � 1.29; 95% CI � (1.20, 1.38)), ECG (RR � 1.37; 95% CI � (1.22, 1.54)), and blood HDL-C level (MD � 0.29 mmol/L; 95% CI � (0.23, 0.35)) compared with TAMs alone from a meta-analysis and systematic review of 14 randomized controlled trials [11]. ere was benefit in the use of Tongxinluo (TXL) capsule for secondary prevention after acute myocardial infarction (AMI).…”
Section: The Therapeutic Effect Of Tcm In Chdmentioning
confidence: 99%
“…Moreover, XFZY can downregulate the expression of Forkhead box (FoxO) genes via silent information regulator 1 (SIRT 1), thus delaying ischemic heart disease [ 20 ]. A systematic review has shown that XFZY plus antianginal drugs is superior to antianginal drugs alone in mitigating symptoms, relieving myocardial ischemia, and decreasing low-density lipoprotein cholesterol (LDL-C) [ 21 ]. However, the review concluded that the included small-scale trials with poor methodological quality do not provide high-quality evidence of XFZY for the treatment of SA.…”
Section: Introductionmentioning
confidence: 99%